2023
DOI: 10.1002/jmor.21557
|View full text |Cite
|
Sign up to set email alerts
|

Muscle architecture and muscle fibre type composition in the forelimb of two African mole‐rat species, Bathyergus suillus and Heterocephalus glaber

Abstract: The scratch-digging Cape dune mole-rat (Bathyergus suillus), and the chisel-toothed digging naked mole-rat (Heterocephalus glaber) are African mole-rats that differ in their digging strategy. The aim of this study was to determine if these behavioural differences are reflected in the muscle architecture and fibre-type composition of the forelimb muscles. Muscle architecture parameters of 39 forelimb muscles in both species were compared. Furthermore, muscle fibre type composition of 21 forelimb muscles were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…[46][47][48] Numerous muscles attached along the scapula and humerus enable the humerus to rotate and the palm to horizontally burrow and push the soil backward, generating a significant burrowing torque. [49][50][51][52] The palm is curved in the center, and the toes are arranged in an arc. This structure not only reduces driving resistance but also facilitates the sliding of soil particles out of the palm.…”
Section: Bioinspired Mechanism Design Philosophymentioning
confidence: 99%
“…[46][47][48] Numerous muscles attached along the scapula and humerus enable the humerus to rotate and the palm to horizontally burrow and push the soil backward, generating a significant burrowing torque. [49][50][51][52] The palm is curved in the center, and the toes are arranged in an arc. This structure not only reduces driving resistance but also facilitates the sliding of soil particles out of the palm.…”
Section: Bioinspired Mechanism Design Philosophymentioning
confidence: 99%
“…Later, Cuthbert (1975) assessed the cranial and forelimb musculature of the same two species, although such descriptions remain unpublished. More recently, Sahd et al (2019Sahd et al ( , 2020 assessed the effects of hind-foot drumming in the hindlimb musculature of three bathyergids, B. suillus, G. capensis, and the common mole-rat Cryptomys hottentotus hottentotus, while Doubell et al (2020) and Sahd et al (2023) assessed differences in the forelimb musculature, muscle architecture and fiber-type composition of B. suillus and the naked mole-rat Heterocephalus glaber. The latter studies reported skeletal and myological differences between such species and attributed them to their distinct digging modes, i.e., the forelimb of B. suillus has relatively larger and additional forelimb muscles with higher muscle mass percentage and more robust bones in comparison to He.…”
mentioning
confidence: 99%
“…The latter studies reported skeletal and myological differences between such species and attributed them to their distinct digging modes, i.e., the forelimb of B. suillus has relatively larger and additional forelimb muscles with higher muscle mass percentage and more robust bones in comparison to He. glaber, suggesting a higher specialization for scratch-digging (Doubell et al, 2020;Sahd et al, 2023). However, such comparison, based on two of the most morphologically and ecologically divergent species within the family (see below), raises several questions, such as whether such differences reflect true morphological adaptations to their digging strategies or rather represent differences in other aspects of their biology (e.g.…”
mentioning
confidence: 99%